2013
DOI: 10.1159/000348617
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive Endothelin-1 and Endothelin A Receptor in Basilar Artery Perivascular Nerves of Young and Adult Capybaras

Abstract: The purpose of this qualitative morphological study was the immunocytochemical and ultrastructural comparison of perivascular nerves of the basilar artery (BA) of young (6-month-old) and adult (12-month-old) capybaras - adult capybaras showed regression of the internal carotid artery (ICA). The study focused on immunolabeling for the vasoactive peptide endothelin-1 (ET-1) and endothelin A receptor (ETA) as well as for the synapse marker synaptophysin (SYP). In the BA of young capybaras, immunoreacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…ET-1-immunoreactive perivascular nerves have previously been revealed in animal (rat, capybara) and human cerebral vasculature (Loesch et al 1998(Loesch et al , 2005Milner 2000a,b;Loesch and Burnstock 2002;Mickey et al 2002). A combined immunocytochemical and electron microscope study of capybara basilar artery also showed the presence of nerve-associated ETA and ETB receptors in addition to those present on the endothelium, smooth muscle and Schwann cells (Loesch et al 2005(Loesch et al , 2013; also see Loesch and Dashwood. 2009) (Fig.…”
Section: Vascular Nervesmentioning
confidence: 99%
“…ET-1-immunoreactive perivascular nerves have previously been revealed in animal (rat, capybara) and human cerebral vasculature (Loesch et al 1998(Loesch et al , 2005Milner 2000a,b;Loesch and Burnstock 2002;Mickey et al 2002). A combined immunocytochemical and electron microscope study of capybara basilar artery also showed the presence of nerve-associated ETA and ETB receptors in addition to those present on the endothelium, smooth muscle and Schwann cells (Loesch et al 2005(Loesch et al , 2013; also see Loesch and Dashwood. 2009) (Fig.…”
Section: Vascular Nervesmentioning
confidence: 99%